2022
DOI: 10.1097/corr.0000000000002322
|View full text |Cite|
|
Sign up to set email alerts
|

Reoperation Rates of Microendoscopic Discectomy Compared With Conventional Open Lumbar Discectomy: A Large-database Study

Abstract: Background Microendoscopic discectomy for lumbar disc herniation has been shown to be as effective as traditional microdiscectomy or open discectomy in terms of clinical outcomes such as pain relief, and it is less invasive. Nevertheless, the reoperation rate for microendoscopic discectomy compared with microdiscectomy or open discectomy remains unclear, possibly due to difficulties in conducting follow-up of sufficient duration and in obtaining information about reoperation in other facilities.Questions/purpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…But it’s a start. The present study by Masuda et al [7] is the first step in this direction; they compared microendoscopic discectomy against open discectomy and traditional microdiscectomy and found that the risk of reoperation was higher among patients who underwent microendoscopic discectomy than among patients who underwent an open discectomy or traditional microdiscectomy at a median follow-up of 4 years after surgery in a large group of patients. Based on this finding, surgeons should make an educated decision about which technique to use and inform their patients accordingly.…”
Section: Where Are We Now?mentioning
confidence: 69%
“…But it’s a start. The present study by Masuda et al [7] is the first step in this direction; they compared microendoscopic discectomy against open discectomy and traditional microdiscectomy and found that the risk of reoperation was higher among patients who underwent microendoscopic discectomy than among patients who underwent an open discectomy or traditional microdiscectomy at a median follow-up of 4 years after surgery in a large group of patients. Based on this finding, surgeons should make an educated decision about which technique to use and inform their patients accordingly.…”
Section: Where Are We Now?mentioning
confidence: 69%
“…These diagnoses, prescriptions, and procedures are coded using the International Classification of Diseases, Tenth Revision (ICD-10) codes, the Anatomical Therapeutic Chemical (ATC) codes together with the Japan-specific YJ (Yakka Joho) codes (code according to the National Health Insurance Drug List), and the Japanese procedure codes. The advantage of the JMDC database is its ability to track an individual’s medical information across different healthcare facilities under the same health insurance, making it widely used for epidemiology studies in Japan (Fukasawa et al, 2023; Masuda et al, 2023; S. Yoshida et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In this retrospective, comparative study of a claims database designed to replicate a case-crossover design [9], which is published in this issue of Clinical Orthopaedics and Related Research ® , the authors isolated patients with hospital-coded pyogenic vertebral osteomyelitis and examined their histories of dental procedures and antibiotic prescriptions. Masuda et al [9] found that dental procedures were not associated with infection, prophylactic antibiotics did not reduce infection risk, and rather paradoxically, the authors found that patients who were not prescribed antibiotics before dental procedures had substantially lower odds of developing pyogenic vertebral osteomyelitis. Based on these discoveries, surgeons might more carefully examine their own prescribing practices.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Although prophylactic antibiotics may prevent infection generally, in patients with a high prevalence of risk factors, Masuda et al [9] found that a claims history of an antibiotic prescription near the time of the proposed inciting event did not change the odds of infection. A similar database study could be performed in a high-risk patient subset who underwent arthroplasty.…”
Section: How Do We Get There?mentioning
confidence: 99%